Molecular Identification of Thermophilic Bacteria Producing Lipase from Two Hot Springs in Perak, Malaysia - S. Noor Suraya; Rafidah Rasol; W. A. R. Wan Razarinah; M. J. Norashirene (International Journal of Integrated Engineering, 2024)
Microbial lipase has been identified as a key biocatalyst in industrial biotechnological applications. Microbial thermostable lipases are excellent candidates because of their capability to survive in high temperatures reaction in industries. The aims of this study were to screen lipolytic activity on Rhodamine B agar; to measure the amount of lipolytic activity through UV-VIS spectrophotometer and to identify the species which have the highest production of lipase enzymes using molecular identification. Two Gram-positive and rod-shaped thermophilic isolates from Ulu Slim (US) and Ara Panjang (AP) were selected. Based on the spectrophotometric assay, isolate AP was a good lipase producer as it produced a higher value of 444.43 U/mL as compared to commercialized lipase. Further molecular identification revealed both isolates as Bacillus sp. Isolate AP was considered as a potential candidate for further studies as the lipase production exceed commercialized lipase production.